Method for improving corrosion resistance of amorphous carbon coating titanium polar plate

By oxidizing the surface of the titanium electrode plate and applying an amorphous carbon coating, the complex and cost-effective method in the prior art is solved, and the corrosion resistance of the titanium electrode plate is significantly improved without reducing conductivity effect.

CN119433439APending Publication Date: 2025-02-14TONGJI UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411640304.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The prior art methods for improving the corrosion resistance of amorphous carbon coated titanium electrode plates are complex and costly, and it is difficult to significantly improve the corrosion resistance without reducing the conductivity.

Method used

The oxide film is prepared by oxidizing the surface of the titanium electrode plate, and then applied to the amorphous carbon coating to improve the corrosion resistance of the coating. The method includes plastic forming of the ultra-thin titanium plate, oxidation treatment and depositing an amorphous carbon coating on its surface.

Benefits of technology

Without reducing the conductivity, the corrosion resistance of the amorphous carbon coated titanium electrode plate is significantly improved, and the cost of the electrode plate is reduced. This method is simple and easy to implement and is suitable for various forming methods.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119433439A_ABST
    Figure CN119433439A_ABST
Patent Text Reader

Abstract

The invention discloses a method for improving the corrosion resistance of an amorphous carbon coating titanium polar plate, which is characterized by comprising the following steps of: carrying out plastic forming on an ultrathin titanium plate to obtain a polar plate semi-finished product; performing oxidation treatment on the pole plate semi-finished product to prepare an oxidation film on the surface of the pole plate semi-finished product; and plating an amorphous carbon coating on the surface of the polar plate semi-finished product with the oxide film for coating treatment to obtain a polar plate finished product. According to the method, the corrosion resistance of the amorphous carbon coating titanium polar plate can be rapidly and effectively improved, an oxidation layer can be rapidly generated on the surface of the titanium polar plate through furnace heating or electric heating, an oxidation film can be generated on the surface of the titanium polar plate in an extremely short time (within 30 minutes, basically within 15 minutes, and even less than 1 minute), the production efficiency is high, and the production cost is low. And in particular, the process does not influence the proceeding of subsequent processes (such as a transition layer), so that the process can be combined with other coating means, and the corrosion resistance and other properties of the coated titanium polar plate are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of fuel cells, and in particular to a method for improving the corrosion resistance of amorphous carbon coated titanium plates. Background Art

[0002] High power, long life and high performance are the development trends of hydrogen proton exchange membrane fuel cells (PEMFC). As one of the core components of hydrogen fuel cells, the corrosion resistance of the plate in the working environment of PEMFC has an important impact on the life of the fuel cell. The U.S. Department of Energy (DOE) stipulates that by 2025, the corrosion rate of hydrogen fuel cell bipolar plates must be less than 1 μA / cm 2 Titanium, which has the advantages of low density, high specific strength and high corrosion resistance, is considered to be an important plate substrate in the future.

[0003] In order to further improve the corrosion resistance and conductivity of the titanium plate, a layer of coating is often added to the surface of the titanium plate. At present, the surface coatings of metal plates mainly include metal-based coatings (precious metals, metal carbon / nitrogen compounds) and carbon-based coatings (graphite, conductive polymers, amorphous carbon, etc.). Carbon-based coatings, especially amorphous carbon coatings, have excellent corrosion resistance and conductivity in the bipolar environment of PEMFC, and excellent hydrophobicity, which is conducive to the discharge of water generated by the reaction. In addition, its relatively low cost has been widely used in actual production. Therefore, further improving the performance of amorphous carbon coatings on this basis is also a current research hotspot. In terms of optimizing the corrosion resistance of amorphous carbon coatings, it can currently be achieved through the following two ways: element doping and preparation of multilayer composite coatings. The method of element doping is to add or modify elements in the original element system of the coating to achieve a method of improving corrosion resistance and conductivity. The preparation of multilayer composite coatings includes: (1) pre-depositing a transition layer on the substrate. The transition layer can reduce the difference in thermal expansion coefficient between the coating material and the substrate, improve the bonding performance between the coating and the substrate, and thus improve the corrosion resistance of the coating; (2) preparing different functional layers of corrosion resistance and conductivity.

[0004] Patent document CN116855900A (a modified carbon-based composite coating and preparation method, bipolar plate) proposes a modified carbon-based composite coating and preparation method, bipolar plate, by doping one or more nitride particles of Cr, Ti, Zr, Mo and Ta in the amorphous carbon coating, the internal compressive stress of the coating can be greatly reduced, the pore defects of the coating can be reduced, and the overall density, conductivity and corrosion resistance of the coating can be improved. Patent document CN113991134A (a kind of amorphous carbon coating for fuel cell metal bipolar plate and preparation method) proposes a method of using physical vapor deposition to sequentially prepare a metal transition layer, a Me / C gradient layer, an amorphous carbon corrosion-resistant layer, and an amorphous carbon conductive layer on the surface of a metal bipolar plate, thereby improving the corrosion resistance and conductivity of the metal plate. Patent document CN115312798A (metal plate surface protective coating and preparation method, application, metal plate) proposes a method for preparing a multi-layer alternating conductive and corrosion-resistant functional layer, which can avoid corrosion of the metal plate and improve the conductivity of the metal plate.

[0005] However, the above methods for improving the corrosion resistance of amorphous carbon coated titanium plates are relatively complicated and inevitably bring a lot of additional costs in terms of materials and equipment. Therefore, developing a new method for improving the corrosion resistance of amorphous carbon coated titanium plates is of great significance to reducing the cost of plates and extending their service life. Summary of the invention

[0006] In view of the shortcomings of the above-mentioned prior art, the present invention aims to provide a simple and fast method for improving the corrosion resistance of amorphous carbon coated titanium plates. An oxide film is prepared on the surface of the titanium plate by oxidation treatment, and then a coating treatment is applied. This can improve the corrosion resistance of the amorphous carbon coated titanium plate without reducing the conductivity.

[0007] To achieve the above object, the new method for improving the corrosion resistance of titanium pole plates according to the present invention comprises the following steps: A method for improving the corrosion resistance of an amorphous carbon coated titanium pole plate comprises the following steps: Plastic forming an ultra-thin titanium plate to obtain a semi-finished plate; the material of the ultra-thin titanium plate is industrial pure titanium with a titanium content greater than 99.5% and a thickness ranging from 0.075 to 0.15 mm; Performing oxidation treatment on the semi-finished plate to prepare an oxide film on its surface; The surface of the semi-finished plate with an oxide film is coated with an amorphous carbon coating to obtain a finished plate; the amorphous carbon coating includes a transition layer and an amorphous carbon layer.

[0008] A method for improving the corrosion resistance of an amorphous carbon coated titanium pole plate comprises the following steps: Plastic forming an ultra-thin titanium plate to obtain a semi-finished plate; the material of the ultra-thin titanium plate is industrial pure titanium with a titanium content greater than 99.5% and a thickness ranging from 0.075 to 0.15 mm; Performing oxidation treatment on the semi-finished plate to prepare an oxide film on its surface; The surface of the semi-finished plate with an oxide film is coated with an amorphous carbon coating to obtain a finished plate; the amorphous carbon coating includes an amorphous carbon layer.

[0009] As a preferred aspect, the oxidation treatment is implemented as follows: quickly preparing an oxide film on the surface of the semi-finished plate by heating in a furnace or by electric heating; The heating temperature range of oxidation treatment is 500~750℃; When the heating method is heating in a furnace, the oxidation treatment time is controlled within the range of 2 to 30 minutes; When the heating method is electric heating, the oxidation treatment time is controlled within the range of 0.5 to 60 seconds; the voltage of the electric heating is 50 to 500 V, and the current frequency is 1 to 4000 Hz.

[0010] As a preferred aspect, the transition layer element is Ti, the thickness is 1-200 nm, and the thickness of the amorphous carbon layer is 150-400 nm.

[0011] As a preferred aspect, the plastic forming means include cold stamping, two-step stamping, and heat-assisted two-step stamping; wherein the cold stamping plastic strain is 15%~30%; the pre-forming plastic strain of the two-step stamping is 5%~20%, and the secondary forming plastic strain is 10%~20%; the pre-forming plastic strain of the heat-assisted two-step stamping is 5%~20%, the annealing heat treatment parameters are 500~750℃, the time is 2~30min, and the secondary forming plastic strain is 10%~20%.

[0012] As a preferred aspect, the amorphous carbon coating is implemented as follows: first, the surface of the semi-finished plate with an oxide film is ultrasonically cleaned with alcohol for 10 minutes, and then plasma etching is performed for 20 minutes with an etching power of 2kW; next, a titanium transition layer is deposited in a chamber with a vacuum degree of 0.005Pa and a temperature of 200°C, with a sputtering power of 18kW for 2 minutes; then the sputtering power is adjusted to 20kW for a duration of 25 minutes to deposit an amorphous carbon layer; finally, the chamber is cooled and ultrasonically cleaned with alcohol for 5 minutes to obtain a finished plate.

[0013] Compared with the prior art, the present invention has the following beneficial effects: The present invention innovatively proposes to perform oxidation treatment on the semi-finished plate before coating to form an oxide film on its surface, which can improve the corrosion resistance of the coated titanium plate without reducing the conductivity; The new method proposed by the present invention can be used simultaneously with the existing method to further improve the corrosion resistance of the coated titanium plate; The present invention is applicable to various forming methods of titanium plates, including but not limited to cold stamping, multi-step stamping, heat-assisted multi-step stamping, etc. The present invention is simple and easy to implement, does not require additional material and equipment costs, and can be directly applied in actual production; The present invention can quickly and effectively improve the corrosion resistance of the amorphous carbon coated titanium pole plate, and can quickly generate an oxide layer on the surface of the titanium pole plate by heating in a furnace or by electric heating. The oxide film can be generated on the surface of the titanium pole plate in a very short time (within 30 minutes, basically within 15 minutes, and electric heating can even be less than 1 minute), and the production efficiency is high. In particular, the present process does not affect the subsequent processes (such as the transition layer), and can be combined with other coating methods to improve the corrosion resistance and other properties of the coated titanium pole plate.

[0014] With reference to the following description and the accompanying drawings, the specific embodiments of the present invention are disclosed in detail, indicating the manner in which the principles of the present invention can be adopted. It should be understood that the embodiments of the present invention are not limited in scope thereby.

[0015] Features described and / or illustrated with respect to one embodiment may be used in the same or similar manner in one or more other embodiments, combined with features in other embodiments, or substituted for features in other embodiments.

[0016] It should be emphasized that the term “include / comprises” when used herein refers to the presence of features, integers, steps or components, but does not exclude the presence or addition of one or more other features, integers, steps or components. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings in the following description are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without paying creative labor.

[0018] Figure 1 It is a Tafel curve of the corrosion performance test of the two-step formed coating titanium plate samples under dynamic voltage conditions, which are not treated, heated and oxidized in the furnace, and electrically heated and oxidized in Examples 1 and 2; Figure 2 The curves of contact resistance between the two-step formed coated titanium plate samples and carbon paper as a function of the pressing force in Examples 1 and 2, which are untreated, heated and oxidized in a furnace, and electrically heated and oxidized.

[0019] Figure 3 It is the contact resistance between the two-step formed coated titanium plate samples and the carbon paper under a compression force of 1.4 MPa in Examples 1 and 2, which are untreated, heated and oxidized in a furnace, and electrically heated and oxidized.

[0020] Figure 4 It is a Tafel curve of the corrosion performance test of the heat-assisted two-step formed coating titanium plate samples under dynamic voltage conditions in Examples 3 and 4, which are not treated, treated by heating oxidation in the furnace, and treated by electric heating oxidation; Figure 5 The cathode constant potential polarization curves of the titanium plate samples of the heat-assisted two-step forming coating in the third and fourth embodiments, which are not treated, treated by heating oxidation in the furnace, and treated by electric heating oxidation, for 1 hour; Figure 6 The curves of contact resistance between the titanium plate sample and the carbon paper as a function of the pressing force are shown in Examples 3 and 4, which are untreated, furnace heated and oxidized, and electrically heated and oxidized.

[0021] Figure 7 It is the contact resistance between the heat-assisted two-step formed coated titanium electrode sample and the carbon paper under a compression force of 1.4 MPa in Examples 3 and 4, which are untreated, treated by heating oxidation in a furnace, and treated by electric heating oxidation. DETAILED DESCRIPTION

[0022] In order to enable those skilled in the art to better understand the technical solutions in the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0023] It should be noted that when an element is referred to as being "disposed on" another element, it may be directly on the other element or there may be another element centered thereon. When an element is considered to be "connected to" another element, it may be directly connected to the other element or there may be another element centered thereon at the same time. The terms "vertical", "horizontal", "left", "right" and similar expressions used herein are for illustrative purposes only and do not represent the only implementation method.

[0024] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.

[0025] The following methods were used to test the corrosion resistance and contact resistance of Examples 1-4: Corrosion resistance is at pH = 3 H 2 SO 4 + 2ppm HF solution and continuously flow O 2 The test temperature was controlled at 80°C in a water bath. The Tafel curve scan range was -0.6 V (vs. Ag / AgCl) to 1.3 V (vs. Ag / AgCl), and the constant potential polarization voltage was 0.6 V (vs. Ag / AgCl).

[0026] The contact resistance is tested on an automatic plate contact resistance tester, and a compression force varying from 0.4 MPa to 2.0 MPa is applied to test the change in contact resistance. Embodiment 1

[0027] In this embodiment, TA1 industrial pure titanium with a thickness of 0.1 mm produced by a Japanese steel plant is used as the substrate. The electrode plate semi-finished product is first prepared through a two-step cold forming process, and then the electrode plate semi-finished product is transferred to a muffle furnace at a temperature of 600°C. After being kept warm for 10 minutes, it is taken out and air-cooled to room temperature. Finally, the electrode plate semi-finished product that has been heated and oxidized in the furnace is transferred to a multi-functional coating machine to deposit an amorphous carbon coating on its surface.

[0028] The multifunctional coating machine can coat the amorphous carbon coating by the following steps: First, the surface of the semi-finished plate with an oxide film is cleaned with ultrasonic alcohol for 10 minutes, and then plasma etching is performed for 20 minutes with an etching power of 2kW; next, a titanium transition layer is deposited in a chamber with a vacuum degree of 0.005Pa and a temperature of 200°C, with a sputtering power of 18kW for 2 minutes; then the sputtering power is adjusted to 20kW for 25 minutes to deposit an amorphous carbon layer; finally, the chamber is cooled and ultrasonic alcohol cleaning is performed for 5 minutes to obtain a finished plate.

[0029] The corrosion resistance and contact resistance of the amorphous carbon-coated titanium plate treated by heating and oxidation in the furnace were tested under dynamic voltage conditions. It was found that the self-corrosion current density was 0.32μA / cm2 compared with the untreated amorphous carbon-coated titanium plate. 2 Reduced to 0.18μA / cm 2( Figure 1 ), while the contact resistance is close to ( Figure 2 and Figure 3 ), under a compression force of 1.4MPa, the average contact resistance of the untreated amorphous carbon coated titanium plate is 6.2mΩcm 2 The average contact resistance of the amorphous carbon-coated titanium plate treated by heating and oxidation in the furnace is 6.7 mΩcm 2 This shows that the new method provided by the present invention can improve the corrosion resistance without affecting the conductivity of the amorphous carbon coated titanium plate. Embodiment 2

[0030] In this embodiment, TA1 industrial pure titanium with a thickness of 0.1 mm produced by a Japanese steel plant is used as the substrate. The pole plate semi-finished product is first prepared through a two-step cold forming process, and then the pole plate semi-finished product is heated by electric current. The heating temperature is 750°C and the current duration is 2s. Finally, the pole plate semi-finished product that has undergone electric heating and oxidation treatment is transferred to a multi-functional coating machine to deposit an amorphous carbon coating on its surface.

[0031] The multifunctional coating machine can coat the amorphous carbon coating by the following steps: First, the surface of the semi-finished plate with an oxide film is cleaned with ultrasonic alcohol for 10 minutes, and then plasma etching is performed for 20 minutes with an etching power of 2kW; next, a titanium transition layer is deposited in a chamber with a vacuum degree of 0.005Pa and a temperature of 200°C, with a sputtering power of 18kW for 2 minutes; then the sputtering power is adjusted to 20kW for 25 minutes to deposit an amorphous carbon layer; finally, the chamber is cooled and ultrasonic alcohol cleaning is performed for 5 minutes to obtain a finished plate.

[0032] The corrosion resistance and contact resistance tests of the amorphous carbon-coated titanium plate treated by electric heating oxidation were carried out under dynamic voltage conditions. It was found that the self-corrosion current density of the amorphous carbon-coated titanium plate was 0.32μA / cm2 compared with that of the untreated amorphous carbon-coated titanium plate. 2 Reduced to 0.16μA / cm 2 ( Figure 1 ), while the contact resistance is close to ( Figure 2 and Figure 3 ), under a compression force of 1.4MPa, the average contact resistance of the untreated 2 The average contact resistance of the electric heating oxidation treatment is 6.5mΩcm 2 This indicates that the electric heating oxidation is also applicable to the new method proposed in the present invention, that is, an oxide film is formed on the surface of the semi-finished plate through oxidation treatment to improve the corrosion resistance of the coated plate. Embodiment 3

[0033] In this embodiment, TA1 industrial pure titanium with a thickness of 0.1 mm produced by a Japanese steel plant is used as the substrate. The electrode plate semi-finished product is first prepared by a heat-assisted two-step forming process, and then the electrode plate semi-finished product is transferred to a muffle furnace at a temperature of 600°C. After being kept warm for 10 minutes, it is taken out and air-cooled to room temperature. Finally, the electrode plate semi-finished product that has been heated and oxidized in the furnace is transferred to a multi-functional coating machine to deposit an amorphous carbon coating on its surface.

[0034] The multifunctional coating machine can coat the amorphous carbon coating by the following steps: First, the surface of the semi-finished plate with an oxide film is cleaned with ultrasonic alcohol for 10 minutes, and then plasma etching is performed for 20 minutes with an etching power of 2kW; next, a titanium transition layer is deposited in a chamber with a vacuum degree of 0.005Pa and a temperature of 200°C, with a sputtering power of 18kW for 2 minutes; then the sputtering power is adjusted to 20kW for 25 minutes to deposit an amorphous carbon layer; finally, the chamber is cooled and ultrasonic alcohol cleaning is performed for 5 minutes to obtain a finished plate.

[0035] The corrosion resistance test of the finished plate of this embodiment ( Figure 4 and Figure 5 ) and contact resistance test ( Figure 6 and Figure 7 ) showed that in the potentiodynamic test, the self-corrosion current density increased from 0.38 μA / cm 2 Reduced to 0.30μA / cm 2 The corrosion current density under static voltage conditions increased from 0.58μA / cm 2 Down to 0.19μA / cm 2 , while the contact resistance is close to that of the untreated average contact resistance of 6.8mΩcm 2 The average contact resistance of the furnace heating oxidation treatment is 6.0mΩcm 2 This indicates that the new method of the present invention can also improve the corrosion resistance of the amorphous carbon-coated titanium plate formed by heat-assisted two-step forming. Embodiment 4

[0036] In this embodiment, TA1 industrial pure titanium with a thickness of 0.1 mm produced by a Japanese steel plant is used as the substrate. The electrode plate semi-finished product is first prepared by a heat-assisted two-step forming process, and then the electrode plate semi-finished product is heated by electric current. The heating temperature is 750°C and the current duration is 2s. Finally, the electrode plate semi-finished product that has undergone electric heating and oxidation treatment is transferred to a multi-functional coating machine to deposit an amorphous carbon coating on its surface.

[0037] The multifunctional coating machine can coat the amorphous carbon coating by the following steps: First, the surface of the semi-finished plate with an oxide film is cleaned with ultrasonic alcohol for 10 minutes, and then plasma etching is performed for 20 minutes with an etching power of 2kW; next, a titanium transition layer is deposited in a chamber with a vacuum degree of 0.005Pa and a temperature of 200°C, with a sputtering power of 18kW for 2 minutes; then the sputtering power is adjusted to 20kW for 25 minutes to deposit an amorphous carbon layer; finally, the chamber is cooled and ultrasonic alcohol cleaning is performed for 5 minutes to obtain a finished plate.

[0038] The corrosion resistance test of the finished plate of this embodiment ( Figure 4 and Figure 5 ) and contact resistance test ( Figure 6 and Figure 7 ) showed that in the potentiodynamic test, the self-corrosion current density increased from 0.38 μA / cm 2 Reduced to 0.28μA / cm 2 The corrosion current density under static voltage conditions increased from 0.58μA / cm 2 Down to 0.18μA / cm 2 , the corrosion resistance is improved, while the contact resistance is close to the average contact resistance of 6.8mΩcm without treatment 2 The average contact resistance of the electric heating oxidation treatment is 5.7mΩcm 2 .

[0039] Any numerical value cited herein includes all values ​​of lower and upper values ​​that increase by one unit from the lower limit to the upper limit, and there is at least a two-unit interval between any lower value and any higher value. For example, if the value of the quantity of a component or a process variable (such as temperature, pressure, time, etc.) is set forth to be from 1 to 90, preferably from 20 to 80, and more preferably from 30 to 70, the purpose is to illustrate that values ​​such as 15 to 85, 22 to 68, 43 to 51, 30 to 32 are also explicitly listed in the specification. For values ​​less than 1, one unit is appropriately considered to be 0.0001, 0.001, 0.01, 0.1. These are merely examples that are intended to be clearly expressed, and it can be considered that all possible combinations of numerical values ​​listed between the lowest value and the highest value are clearly set forth in the specification in a similar manner.

[0040] Unless otherwise indicated, all ranges include the endpoints and all numbers between the endpoints. "About" or "approximately" used with a range applies to both endpoints of the range. Thus, "about 20 to 30" is intended to cover "about 20 to about 30", including at least the specified endpoints.

[0041] All articles and references disclosed, including patent applications and publications, are incorporated herein by reference for all purposes. The term "consisting essentially of..." to describe a combination should include the identified elements, ingredients, parts or steps and other elements, ingredients, parts or steps that do not substantially affect the basic novel characteristics of the combination. The use of the terms "comprising" or "including" to describe a combination of elements, ingredients, parts or steps herein also contemplates embodiments that consist essentially of these elements, ingredients, parts or steps. By using the term "may", it is intended to indicate that any attribute described that "may" include is optional.

[0042] Multiple elements, ingredients, parts or steps can be provided by a single integrated element, ingredient, part or step. Alternatively, a single integrated element, ingredient, part or step can be divided into separate multiple elements, ingredients, parts or steps. The disclosure "one" or "an" used to describe an element, ingredient, part or step is not intended to exclude other elements, ingredients, parts or steps.

[0043] It should be understood that the above description is for illustration and not for limitation. Many embodiments and many applications beyond the examples provided will be apparent to those skilled in the art upon reading the above description. Therefore, the scope of the present teachings should not be determined with reference to the above description, but should be determined with reference to the appended claims and the full scope of equivalents possessed by such claims. For the purpose of comprehensiveness, all articles and references, including disclosures of patent applications and publications, are incorporated herein by reference. The omission of any aspect of the subject matter disclosed herein in the preceding claims is not intended to be a waiver of the subject matter, nor should it be considered that the inventors did not consider the subject matter to be part of the disclosed inventive subject matter.

Claims

1. A method for improving the corrosion resistance of amorphous carbon coated titanium pole plates, characterized in that: The following steps are involved: Plastic forming an ultra-thin titanium plate to obtain a semi-finished plate; the material of the ultra-thin titanium plate is industrial pure titanium with a titanium content greater than 99.5% and a thickness ranging from 0.075 to 0.15 mm; Performing oxidation treatment on the semi-finished plate to prepare an oxide film on its surface; The surface of the semi-finished plate with an oxide film is coated with an amorphous carbon coating to obtain a finished plate; The amorphous carbon coating includes a transition layer and an amorphous carbon layer.

2. A method for improving the corrosion resistance of amorphous carbon coated titanium pole plates, characterized in that: The following steps are involved: Plastic forming an ultra-thin titanium plate to obtain a semi-finished plate; the material of the ultra-thin titanium plate is industrial pure titanium with a titanium content greater than 99.5% and a thickness ranging from 0.075 to 0.15 mm; Performing oxidation treatment on the semi-finished plate to prepare an oxide film on its surface; The surface of the semi-finished plate with an oxide film is coated with an amorphous carbon coating to obtain a finished plate; The amorphous carbon coating layer includes an amorphous carbon layer.

3. The method for improving the corrosion resistance of amorphous carbon coated titanium pole plate according to claim 1 or 2, characterized in that: The oxidation treatment is implemented as follows: quickly preparing an oxide film on the surface of the semi-finished plate by means of furnace heating or electric heating; The heating temperature range of oxidation treatment is 500~750℃; When the heating method is heating in a furnace, the oxidation treatment time is controlled within the range of 2 to 30 minutes; When the heating method is electric heating, the oxidation treatment time is controlled within the range of 0.5 to 60 seconds; the voltage of the electric heating is 50 to 500 V, and the current frequency is 1 to 4000 Hz.

4. The method for improving the corrosion resistance of amorphous carbon coated titanium pole plate according to claim 3, characterized in that: The transition layer element is Ti, the thickness is 1-200nm, and the thickness of the amorphous carbon layer is 150-400nm.

5. The method for improving the corrosion resistance of amorphous carbon coated titanium pole plate according to claim 3, characterized in that: The plastic forming means is selected from one of cold stamping, two-step stamping and heat-assisted two-step stamping; among them, the plastic strain of cold stamping is 15%~30%; the pre-forming plastic strain of two-step stamping is 5%~20%, and the secondary forming plastic strain is 10%~20%; the pre-forming plastic strain of heat-assisted two-step stamping is 5%~20%, the annealing heat treatment parameters are 500~750℃, the time is 2~30min, and the secondary forming plastic strain is 10%~20%.

6. The method for improving the corrosion resistance of amorphous carbon coated titanium pole plate according to claim 3, characterized in that: The amorphous carbon coating is implemented as follows: first, the surface of the semi-finished plate with an oxide film is ultrasonically cleaned with alcohol for 10 minutes, and then plasma etching is performed for 20 minutes with an etching power of 2kW; next, a titanium transition layer is deposited in a chamber with a vacuum degree of 0.005Pa and a temperature of 200°C, with a sputtering power of 18kW for 2 minutes; then the sputtering power is adjusted to 20kW, the duration is 25 minutes, and an amorphous carbon layer is deposited; finally, the chamber is cooled and ultrasonically cleaned with alcohol for 5 minutes to obtain a finished plate.

Citation Information

Patent Citations

  • Amorphous carbon coating for fuel cell metal bipolar plate and preparation method of amorphous carbon coating

    CN113991134A

  • Metal pole plate surface protective coating, preparation method and application thereof and metal pole plate

    CN115312798A

  • Modified carbon-based composite coating, preparation method and bipolar plate

    CN116855900A